2022
DOI: 10.3389/fnhum.2022.901422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Slides and Video Clips as Different Methods for Inducing Emotions: An Electroencephalographic Alpha Modulation Study

Abstract: Films, compared with emotional static pictures, represent true-to-life dynamic stimuli that are both ecological and effective in inducing an emotional response given the involvement of multimodal stimulation (i.e., visual and auditory systems). We hypothesized that a direct comparison between the two methods would have shown greater efficacy of movies, compared to standardized slides, in eliciting emotions at both subjective and neurophysiological levels. To this end, we compared these two methods of emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
3
6
0
Order By: Relevance
“…A similar pattern of findings was also observed in previous research using dynamic stimuli (film clips, or looming stimuli), in which it was reported that emotional stimuli trigger a greater alpha sustained decrease compared to neutral stimuli (Kim et al, 2021; Romeo et al, 2022; Sarlo et al, 2005; Vagnoni et al, 2015). The impact of unpleasant film clips on oscillatory activity was investigated by Sarlo et al (2005) who wanted to clarify the specificity of alpha changes induced by different unpleasant contents.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar pattern of findings was also observed in previous research using dynamic stimuli (film clips, or looming stimuli), in which it was reported that emotional stimuli trigger a greater alpha sustained decrease compared to neutral stimuli (Kim et al, 2021; Romeo et al, 2022; Sarlo et al, 2005; Vagnoni et al, 2015). The impact of unpleasant film clips on oscillatory activity was investigated by Sarlo et al (2005) who wanted to clarify the specificity of alpha changes induced by different unpleasant contents.…”
Section: Introductionsupporting
confidence: 87%
“…Consistently, this pattern of ERD findings has been observed not only with pictures but also with other emotional reactivity induction techniques, such as film clips (Romeo et al, 2022). Romeo et al (2022) reported a larger alpha ERD for erotic and fear-inducing film clips compared to neutral ones, and, in addition, a larger alpha ERD for erotic compared to fear-inducing film clips over posterior regions. Although picture repetition does not affect the alpha ERD for either pleasant or unpleasant stimuli, an enhanced alpha ERD has been observed when novel emotional stimuli (pleasant and unpleasant), but not neutral ones, are presented after an extensive phase of stimulus repetition.…”
Section: Negative Bias In Affective Modulation Of Alpha Erd?supporting
confidence: 79%
See 1 more Smart Citation
“…The differences emerged in the last decades of research (e.g., engagement of left versus right regions; contribution of different EEG rhythms) may depend on the kind of stimuli used for inducing emotional reactions (e.g., pictures, faces, clips). Notably, the presentation of static pictures and dynamic clips elicited different EEG patterns of activation in the same group of participants (Romeo et al., 2022). Moreover, ecological and multimodal materials (e.g., movie clips) are more effective in prompting subjective and physiological emotional responses compared to images (Gross & Levenson, 1995; Palomba et al., 2000; Rottenberg et al., 2007; Schaefer et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Source localization was computed by means of sLORETA, the most widely used approach in the field because of its accuracy and speed of computation (Asadzadeh et al., 2020; Pascual‐Marqui, 2002). sLORETA is also widely used in emotional research (Ertl et al., 2013; Maffei et al., 2019; Romeo et al., 2022; Romeo & Spironelli, 2023).…”
Section: Introductionmentioning
confidence: 99%